ANALISA TEMPORAL PERUBAHAN LUAS HUTAN MANGROVE DI KABUPATEN SIDOARJO DENGAN MEMANFAATKAN DATA CITRA SATELIT - Zainul Hidayah (Bumi Lestari Journal of Environment, 2013)
AbstractMangrove forests are one of the coastal ecosystems that have significant ecological andeconomical value. This ecosystem is known for its role in protecting coastal environmentagainst waves and storms as well as supporting the life of numerous marine organisms.However, the increase of human population and the need to expand settlements and industrialareas makes many mangrove ecosystems vulnerable. Objectives of this research were tomeasure the change of mangrove’s area of Sidoarjo district using satellite imagery datafrom different period and to classify the area based on their vegetation density. To measurethe density of mangrove vegetation NDVI index were employed. Results of Landsat ETM-7(acquisition 2002) and ALOS (acquisition 2010) analysis showed that mangrove’s area ofSidoarjo district has declined intensively. Illegal logging and land use changing weresuggested to be the main cause of the destruction of mangrove forest in this area. In order toprevent further destruction of the mangrove’s area, local authorities have implemented UUNo.27 where heavy penalties are implied for illegal logging.